1984
DOI: 10.1007/bf00541938
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of mephenytoin: A new drug hydroxylation polymorphism in man

Abstract: Inherited deficiency in mephenytoin hydroxylation was observed in a family study. It is important that the propositus was of the extensive metabolizer phenotype for the genetically controlled hydroxylation of debrisoquine. Thus, a genetic polymorphism of drug hydroxylation was suspected for mephenytoin. A population study of mephenytoin hydroxylation, combined with identification of extensive and poor debrisoquine hydroxylation phenotypes, was carried out in 221 unrelated normal volunteers. Twelve of them (5%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
145
0
3

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(154 citation statements)
references
References 27 publications
6
145
0
3
Order By: Relevance
“…Although several authors (Kupfer & Preisig, 1984;Nakamura et al, 1985;Penno & Vesell, 1983) have considered that the position of the antimode within a bi-modal distribution is indicated by a sharp breakpoint in a probit plot, we have shown that this is not the case. The existence of a sharp breakpoint will depend upon the relative variances of the component distributions and its position will not coincide with that of the antimode (Figure 2e, f).…”
Section: Discussionmentioning
confidence: 66%
“…Although several authors (Kupfer & Preisig, 1984;Nakamura et al, 1985;Penno & Vesell, 1983) have considered that the position of the antimode within a bi-modal distribution is indicated by a sharp breakpoint in a probit plot, we have shown that this is not the case. The existence of a sharp breakpoint will depend upon the relative variances of the component distributions and its position will not coincide with that of the antimode (Figure 2e, f).…”
Section: Discussionmentioning
confidence: 66%
“…42,45 Now these results can be clearly explained by interethnic variations in the CYP2C19 genotype. Among North American and European populations, 56.7-81.0% of patients are homo-EMs, 18.0-37.2% are hetero-EMs, and PMs are less than 6.1%, [46][47][48][49][50] and thus omeprazole 40 mg is required to achieve stronger gastric acid suppression than H 2 -RAs. However, in Orientals, homo-EMs are only 27.7-38.2% and the rest of the population has an intermediate or reduced capacity to metabolize omeprazole; 30,[51][52][53] and therefore strong gastric acid suppression can be obtained even with omeprazole 20 mg or less.…”
Section: Discussionmentioning
confidence: 99%
“…The human CYP2C subfamily consists of at least 4 members (CYP2C8, CYP2C9, CYP2C18, CYP2C19) [1,2]. Extensive metabolizer (EM) and poor metabolizer (PM) polymorphism for mephenytoin [3,4] is well known and has been studied extensively. It has been shown that CYP2C19 is a candidate for mephenytoin 4'-hydroxylation [5,6].…”
Section: Introductionmentioning
confidence: 99%